3D Deployment of Unmanned Aerial Vehicle-Base Station Assisting Ground-Base Station. (17th August 2021) - Hayajneh, Khaled F.; Bani-Hani, Khaled; Shakhatreh, Hazim; Anan, Muhammad; Sawalmeh, Ahmad
Abstract : Unmanned aerial vehicles (UAVs), also named as drones, have become a modern model to provide a quick wireless communication infrastructure. They have been used when conventional base stations' capacity is suffering in some extreme cases such as congestion inside the cell or a special event. This paper proposes an efficient three-dimension (3D) placement of a single UAV-assisted wireless network in such cases. Our proposed model assists the ground base station (GBS) using the UAV to serve arbitrary distributed users considering the impact of the obstacle blockage over the well-known air-to-ground (A2G) path model. This work is aimed at optimizing the percentage of available bandwidth that must be provided to the UAV in order to maximize the number of served users. In addition, it finds the 3D placement of the UAV base station (UAVBS) that maximizes the number of served users, each with maximum quality-of-service (QoS). The exhaustive search and particle swarm optimization (PSO) algorithms are used to find the problem's solution.